Pengembangan Media Crossword Puzzle Berbasis HOTS pada Pembelajaran Tematik - Kusuma, Elisabet Dyah (Jurnal Didaktika Pendidikan Dasar, 2021)
The development of hots-based Crossword puzzle media in thematic learning aims to improve critical thinking skills in elementary school students, so that there will be an increase in students’ critical thinking skills and an increase in student learning outcomes at SD Negeri Gadingan 02, Mojolaban District, Sukoharjo Regency. This innovation is developed by applying research and development methods. The results obtained show that the percentage of student learning outcomes has increased, from before the use of HOTS-Based Crossword Puzzle media was obtained an average of 50.02%, then increased during trial 1 to 56.18% and increased in trial 2 to 78, 75%. The conclusion obtained on the achievement of the increase that occurs due to the use of hots-based Crossword puzzle media is that the activeness of students in using HOTS-based Crossword puzzle media is a step in increasing critical thinking skills of thematic learning.